Faunistic Study of Hover Flies (Diptera: Syrphidae) of Pakistan. (3rd July 2017) - Shehzad, Anjum; Ghorpadé, Kumar; Rafi, Muhammad Ather; Zia, Ahmed; Bhatti, Abdul Rauf; Ilyas, Muhammad; Shah, Syed Waqar
Abstract: The present study is based mainly on specimens of syrphid flies collected in Pakistan during country-wide surveys made from 2009 to 2014. These results are supplemented by known records of Syrphidae of Pakistan documented by various authorities earlier. These results yielded 71 species of 40 genera from Pakistan. Of these, 11 species viz., Paramixogaster contractus (Brunetti, 1923) Eoseristalis albibasis (Bigot, 1880), Mesembrius quadrivittatus (Wiedemann, 1819), Eumerus nepalensis Brunetti, 1908, Eumerus sexvittatus Brunetti, 1915, Psilota cyanea Hill, 1921, Volucella peleterii Macquart, 1834 Volucella ruficauda Brunetti, 1907, Chrysotoxum antiquum Walker, 1852, Syrphus vitripennis Meigen, 1822 and Xanthogramma pedissequum (Harris, 1776), are first records for Pakistan.